Knowledge mapping and current trends of Warburg effect in the field of cancer - Zhao, Quan; Wang, Lina; Lv, Zongwei; Wang, Xia; Xu, Zhenqun; Wang, Kefeng (Frontiers in Oncology, 2023)
Background: Since abnormal aerobic glycolysis was first identified in cancer cells, many studies have focused on its mechanisms. The purpose of this study was to analyze the global research status of the Warburg effect in cancer using bibliometrics. Methods: Articles published from 01 January 2013 to 31 December 2022 (n=2,067) were retrieved from the Web of Science core collection database and analyzed using VOSviewer and CiteSpace software. Results: Over the past decade, there was an overall increase in the number of annual publications. China was the most productive country with 790 articles, while the United States received the most citations, with 25,657 citations in total. Oncotarget was the most productive and most cited journal, with 99 articles and 4,191 citations, respectively. International cooperation was common, with the USA cooperating most with other countries. Lactate metabolism, citrate production, and non-coding RNAs related to the Warburg effect have received increasing attention in cancer research. These areas may become future research trends. Conclusion: The study findings help summarize the research status and hotspots of the Warburg effect cancer, and will inform subsequent research.